Point data pre-processing based on fuzzy logic for reverse engineering modelling - Budak, Igor (Strojniški vestnik, 2009)
State of the art 3D-digitization systems designed for reverse engineering (RE)modelling are characterized by increased scanning speed and also by the possibility to generate a large number of points in a short time. Generally, this improves the efficiency of the RE-modelling process. In practice however,a significant number of points in the stage of the CAD model generation may become an issue. In addition, the 3D-digitization process is often connected with measuring errors because of the properties of measuring systems and/or the object. Therefore, nowadays considerable attention is devoted to the problem of pre-processing the results of 3D-digitization, often by means of tools of artificial intelligence. This paper introduces a pre-processing system based on fuzzy logic, along with the results of its practical application.
Keywords: obratno inženirstvo; procesiranje; digitalizacija; digitization; umetna inteligenca